PENGARUH PENGGUNAAN APLIKASI IPUSNAS PADA PENGIKUT @LITERARYBASE DI TWITTER TERHADAP MINAT MEMBACA BUKU DIGITAL - Kala, Ynez; Ulina, Ruth Mei (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Advances in technology today, change aspects of Indonesian people's lives. Including digitization of literacy. Nowadays, many readers choose to read books digitally. There are various choices of digital reading applications. One of them is iPusnas, a free reading application managed by the Indonesian National Library. This study aims to determine the effect of using the iPusnas application on @Literarybase followers on Twitter on their interest in reading digital books. The @Literarybase account is a reading community account in Indonesia, which has hundreds of thousands of followers. The research method used is a quantitative descriptive approach. Sampling in this study used a non-probability technique involving 405 respondents. The variables of this research are "The Influence of the Use of iPusnas Applications" with the theory of Uses and Gratification and the application of the concept of The Golden Rules of User Interface (Variable X) and also "Interest in Reading Digital Books" (Variable Y). The results of statistical descriptive research on the variables of the influence of the use of the iPusnas application include Place Users in Control (83.2%), Reduce Users Memory Load (77.8%) and Make The Interface Consistent (79%). The average of these variables can be categorized as good. Variable Y “Interest in Reading Digital Books” has dimensions of Feeling (90.8%), Attention dimension (83.8%) and Motivation dimension (82%). This variable can be categorized as very good. Based on data processing, the two variables show a linear relationship, so that the use of the iPusnas Application has an effect on Interest in Reading Digital Books Key Words: iPusnas Application, The Interest of Reading a Digital Book, e-book